Intellectual capital and financial performance of entrepreneurs in the hotel industry - Ognjanović, Jasmina; Slavković, Marko (Hotel and Tourism Management, 2022)
Intellectual capital is recognized as a key factor in creating value and gaining and maintaining a competitive advantage among service companies. Intellectual capital can be a useful tool for improving the entrepreneurial performance if it is managed properly. The existing literature does not provide enough insight about the role and importance of intellectual capital among entrepreneurs in the hotel industry. The main goal of the paper is to identify the relationship between intellectual capital and financial performance of entrepreneurs in the hotel industry. The descriptive statistics, correlation analysis and multiple regression analysis were applied. Based on the applied statistical methods, it is concluded that intellectual capital has an impact on operating profit and productivity of entrepreneurs in the hotel industry. The results also indicate that human capital had the greatest contribution to improving the financial performance of entrepreneurs in the hotel industry.